Relations between environmental quality and quality of life in Metropolitan Lima - Cabrera Carranza, Carlos (2002)
The present work establishes environmental quality and life quality relations through quality rates. These rates are determined by evaluating quadratic matrixes and indicators. The PM-10, SO2 levels, and lead in PM10 found during the working period (April-December 2001), overrun the maximum limits permitted by the World Health Organization (WHO), as well as the national air environmental quality standards for Peru, which not only determines a decreasing in air quality, but rather gives rise to a decreasing in the populations’s life quality, having consequences on their health and impairing the city’s landscape. The Optimum Quality Rate (OQR) for Metropolitan Lima area is of the order of 101.5, and the Integrated Life Quality Rate (ILQR) is 68.55, what shows that environmental factors influence decisively on the quality of life of Lima inhabitants.